(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Relevance of the study. The thymus (thymus gland) is a large lymphoid organ. The mass of the thymus can reach 37-40 g by adulthood. Maturation and subsequent differentiation of the largest population of T–lymphocytes (thymus-dependent lymphocytes) takes place in this organ. Structurally, the thymus consists of large lobes covered with a connective tissue capsule. Flat partitions extending from the capsule into the thymus divide the thymus tissue into small segments 1-2 mm in size. The lobule is a structural unit of the thymus. The main mass of thymus lymphocytes (cortical zone) is located on the periphery of the lobule. Towards the center, the concentration of lymphocytes is lower (the brain area). Progenitor cells (medium lymphocytes, lymphoblasts), which came with the blood flow from the bone marrow, are localized on the periphery of the thymus lobule and actively divide, forming many small lymphocytes. Maturing, lymphocytes enter the medulla, from where mature T cells enter small venous vessels and are carried with the blood flow throughout the body. The thymus gland is located directly behind the handle of the sternum. Due to the topography of the thymus gland in congenital heart defects, a thymectomy is performed to improve the visualization of heart structures [1.3.5].